Responsibility of the Municipalities - Soto Kloss, Eduardo (Derecho Público Iberoamericano, 2020)
This is a very recent ruling by the Supreme Court, which rejects a substantive cassation deduced by the plaintiff in the process of municipal responsibility (Article 152) of the Constitutional Organic Law of Municipalities (Law No. 18695).